1984
DOI: 10.1152/ajprenal.1984.247.2.f370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an osmotic gradient on antidiuretic hormone-induced endocytosis and hydroosmosis in the toad urinary bladder

Abstract: The luminal (apical) border of the epithelium of the bladder in the well-hydrated toad is relatively impermeable, so the bladder usually stores hyposmotic urine. When antidiuretic hormone (ADH) increases apical membrane osmotic permeability dramatically, water is resorbed from hyposmotic mucosal solution; in the presence of hyposmotic or isosmotic mucosal solutions, ADH concomitantly induces exocytosis at the apical border of granule-rich (G) cells. Then ADH induces endocytosis at this border. We describe how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…A combination of morphological (20) and tissue capacitance (21) measurements has demonstrated that ADH stimulation causes a 10-30% increase in apical membrane surface area with a time course paralleling the rise in tissue Pf. In a similar fashion, termination ofADH stimulation results in a prompt decrease in tissue Pfand concomitant retrieval ofgranular cell apical membrane in the form ofendocytic vesicles (6,18,20,22) containing particle aggregates (23).…”
Section: Vesicles Deliver and Remove Adh Water Channels From The Apicmentioning
confidence: 83%
See 1 more Smart Citation
“…A combination of morphological (20) and tissue capacitance (21) measurements has demonstrated that ADH stimulation causes a 10-30% increase in apical membrane surface area with a time course paralleling the rise in tissue Pf. In a similar fashion, termination ofADH stimulation results in a prompt decrease in tissue Pfand concomitant retrieval ofgranular cell apical membrane in the form ofendocytic vesicles (6,18,20,22) containing particle aggregates (23).…”
Section: Vesicles Deliver and Remove Adh Water Channels From The Apicmentioning
confidence: 83%
“…This conclusion is based on data showing that (a) there is no luminal acidification of WCV in vitro after addition of ATP (26,27,34), (b) measurements of these vesicles in situ using the 342,4-dinitroanilino)-3'-amino-n-methyldipropylamine (DAMP) method show their lumens are not acidic (6), and (c) immunoblots of purified WCV proteins with anti-proton pump antisera reveal these vesicles do not contain the major subunits of the H' ATPase necessary for activity (35). Factors that modulate retrieval of water channels include ADH removal (6,18,20), the magnitude of a transepithelial osmotic gradient (22,27,36), and cytoplasmic dilution or cell swelling (37). Water channel vesicle endocytosis has recently been associated with changes in the phosphorylation state ofa vesicle-associated 1 5.5-kD protein (38).…”
Section: Vesicles Deliver and Remove Adh Water Channels From The Apicmentioning
confidence: 99%
“…Previous studies have demonstrated that granular cell uptake of fluid phase markers from the mucosal bathing solution during continuous ADH stimulation is greatly enhanced by an osmotic gradient (25,26). In addition, freeze-fracture electron microscopic studies have shown that the number of particle aggregates and aggrephore fusion events in the granular cell membrane is decreased by a transepithelial osmotic gradient during both ADH stimulation (20,21) and the period immediately after hormone removal (21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
“…The tracers are found largely in tubular vesicles and multivesicular bodies (25). However, other reports (4,21) disagree as to the importance of apical membrane retrieval during continuous ADH stimulation in the presence of an osmotic gradient.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation